New KSK line of duty - Husna, Hashim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
6 April 2010. The AGM of Human Sciences Club or Kelab Sains Kemanusiaan (KSK) was held to mark the inauguration of the new line up of leaders. Nevertheless, the centre extends its gratitude to the previous leadership of the club who had contributed their outstanding effort since the establishment of the club.